Characteristics of Avicennia lanata (Ridley) Species for mangrove restoration on the coast of North Gorontalo - Faizal Kasim (Tomini Journal of Aquatic Science, 2022)
Research on the rare mangrove Avicennia lanata (Ridley) is based on the habitat affinity of this species on the coast of North Gorontalo observed during 2017-2019. The current search was carried out in geographically isolated areas (land and islands) using a combination of tracking and Point Centered Quarter (PCQ) techniques to observe the substrate condition and elevation of the mangrove patch habitat, as well as to observe the morpho-anatomical character of the stand. The results showed that the habitat affinity of A. lanata species in North Gorontalo covers a wide range of substrate types, including mud, sandy mud, sand, muddy sand, and sandy and muddy soil on land with an elevation of 5.11–6.57 MDPL. The morpho-anatomical character as a distinguishing feature of A. lanata species from other Avicennia species found in leaves, stems, and fruit, could only be observed clearly in individual stands and trees. This study recommends restoration/monitoring of mangrove species A. lanata (Ridley) with a mixed-species restoration approach and community-based co-planting in a long-term mangrove restoration program in the coastal area of North Gorontalo.